2000
DOI: 10.4049/jimmunol.165.10.5906
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligodeoxynucleotides Can Reverse Th2-Associated Allergic Airway Responses and Alter the B7.1/B7.2 Expression in a Murine Model of Asthma

Abstract: CpG oligodeoxynucleotides (CpG-ODN) administered during Ag sensitization or before Ag challenge can inhibit allergic pulmonary inflammation and airway hyperreactivity in murine models of asthma. In this study, we investigated whether CpG-ODN can reverse an ongoing allergic pulmonary reaction in a mouse model of asthma. AKR mice were sensitized with conalbumin followed by two intratracheal challenges at weekly intervals. CpG-ODN was administered 24 h after the first Ag challenge. CpG-ODN administration reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
78
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 40 publications
7
78
0
2
Order By: Relevance
“…The results of RT-PCR showed that the expression of CD86 and TIM-4 mRNAs in LDCs was suppressed by josamycin and spiramycin, but not by midecamycin. Our observation that suppression of CD86 expression was correlated with that of Th2 cell development is similar to the findings of Serebrisky et al (26), and was compatible with the fact that CD86, but not CD80, preferentially costimulates the initial production of IL-4 (27). However, since the levels of expression of CD86 mRNA did not necessarily correlate with those of TIM-4 mRNA, as was the case for treatment with 14-and 15-membered ring macrolide antibiotics, the suppression of CD86 expression induced by josamycin and spiramycin might be associated with suppression of Th1 cell, rather than Th2 cell, development as suggested by Whelan et al (28).…”
Section: Discussionsupporting
confidence: 81%
“…The results of RT-PCR showed that the expression of CD86 and TIM-4 mRNAs in LDCs was suppressed by josamycin and spiramycin, but not by midecamycin. Our observation that suppression of CD86 expression was correlated with that of Th2 cell development is similar to the findings of Serebrisky et al (26), and was compatible with the fact that CD86, but not CD80, preferentially costimulates the initial production of IL-4 (27). However, since the levels of expression of CD86 mRNA did not necessarily correlate with those of TIM-4 mRNA, as was the case for treatment with 14-and 15-membered ring macrolide antibiotics, the suppression of CD86 expression induced by josamycin and spiramycin might be associated with suppression of Th1 cell, rather than Th2 cell, development as suggested by Whelan et al (28).…”
Section: Discussionsupporting
confidence: 81%
“…The decrease in the number of infiltrating eosinophils was shown to occur in a dosedependent fashion when CpG ODN was administered in conjunction with Ag. A high dose of CpG ODN reduced Th2-associated inflammation without the coadministration of Ag, supporting another laboratory's evidence indicating that CpG ODN is able to reverse allergic responses high doses [35]. Taken together with our present observation that the CpG ODN administration does not saliently alter the expression of IFN-c mRNA at the local inflammatory skin, the postulated effects of CpG ODN seem to include both direct and indirect effects on the commitment of Th1 lymphocytes.…”
Section: Discussionsupporting
confidence: 77%
“…3 For example, TLR9 activation by hypomethylated CpG oligodeoxynucleotides or CpG shifts immune responses away from Th2-type toward Th1-type immune responses 4 ; this shift at least partially contributes to the inhibitory effect of CpG in experimental allergic asthma models. [5][6][7][8] Unlike the findings in experimental models, promoting TLR9 activation with CpG has had limited therapeutic success in clinical asthma. 9 An explanation for the disparity between CpG effects in experimental and clinical disease presumably involves multiple factors, such as species differences in the cellular distribution of TLR9 10 and differential effects of mouseversus human-specific CpG.…”
mentioning
confidence: 99%